A two-step method for identifying photopigment opsin and rhodopsin gene sequences underlying human color vision phenotypes - Atilano, Shari R; Kenney, M Cristina; Briscoe, Adriana D; Jameson, Kimberly A (Molecular vision, 2020)
To present a detailed, reliable long range-PCR and sequencing (LR-PCR-Seq) procedure to identify human opsin gene sequences for variations in the long wavelength-sensitive ( ), medium wavelength-sensitive ( ), short wavelength-sensitive ( ), and rhodopsin ( ) genes. Color vision was assessed for nine subjects using the Farnsworth-Munsell 100 hue test, Ishihara pseudoisochromatic plates, and the Rabin cone-contrast threshold procedure (ColorDX, Konan Medical). The color vision phenotypes were normal trichromacy (n = 3), potential tetrachromacy (n = 3), dichromacy (n = 2), and unexplained low color vision (n = 1). DNA was isolated from blood or saliva and LR-PCR amplified into individual products: (4,045 bp), (4,045 bp), (3,326 bp), and (6,715 bp). Each product was sequenced using specific internal primer sets. Analysis was performed with Mutation Surveyor software. The LR-PCR-Seq technique identified known single nucleotide polymorphisms (SNPs) in and gene codons (180, 230, 233, 277, and 285), as well as those for lesser studied codons (174, 178, 236, 274, 279, 298 and 309) in the and genes. Additionally, six SNP variants in the and genes not previously reported in the NCBI dbSNP database were identified. An unreported poly-T region within intron 5(c.36+126) of the gene was also found, and analysis showed it to be highly conserved in mammalian species. This LR-PCR-Seq procedure (single PCR reaction per gene followed by sequencing) can identify exonic and intronic SNP variants in , , , and genes. There is no need for restriction enzyme digestion or multiple PCR steps that can introduce errors. Future studies will combine the LR-PCR-Seq with perceptual behavior measures, allowing for accurate correlations between opsin genotypes, retinal photopigment phenotypes, and color perception behaviors.